Booms and Busts in EMU - Nils Gottfries (Uppsala University, Department of Economics, 2003)
A floating exchange rate combined with a clear inflation target can be a powerful stabilizer even if there are fluctuations in exchange rates that are unrelated to current fundamentals. Under plausible conditions, most of the stabilisation will occur through the exchange rate, and fundamental shocks will generate considerable medium term exchange rate volatility. The consequences of asymmetric shocks inside EMU are worse than envisaged in early analyses of the EMU project such as Calmfors et al. (1997). Inflation and real interest rate differentials arise which magnify the imbalances and cause boom-bust cycles in the member countries.
urn:nbn:se:uu:diva-4504
Keywords: E31; E32; E42; F41; 330; optimal currency area; imperfect competition; interest parity; real interest rate; Eurozone; Optimaler Währungsraum; Schock; Theorie